Neurobiology of cognitive abilities in early childhood autism - Kristina Denisova (Wiley, 2024)
Abstract This perspective considers complexities in the relationship between impaired cognitive abilities and autism from a maturational, developmental perspective, and aims to serve as a helpful guide for the complex and growing investigation of cognitive abilities and Autism Spectrum Disorder (ASD). Low Intelligence Quotient (IQ) and ASD are frequently co‐occurring. About 37% of 8‐year old children and 48% of 4‐year old children diagnosed with ASD also have Intellectual Disability, with IQ below 70. And, low IQ in early infancy, including below 1 year of age, carries a 40% greater chance of receiving ASD diagnosis in early childhood. We consider the evidence that may explain this co‐occurrence, including the possibility that high IQ may "rescue" the social communication issues, as well as the possible role of critical periods during growth and development. We consider how early low IQ may subsume a part of a subgroup of individuals with ASD, in particular, those diagnosed with autism in very early childhood, and we provide neurobiological evidence in support of this subtype. Moreover, we distinguish the concept of early low IQ from the delay in speech onset in preschool and school‐aged children, based on (i) age and (ii) impairments in both verbal and non‐verbal domains. The etiology of these early‐diagnosed, early low IQ ASD cases is different from later‐diagnosed, average or higher‐IQ cases, and from children with speech delay onset. Given recent interest in formulating new subtypes of autism, rather than continuing to conceive of ASD as a spectrum, as well as new subtypes that vary in the degree of severity along the spectrum, we identify gaps in knowledge and directions for future work in this complex and growing area.